Advanced Graft Development Approaches for ACL Reconstruction or Regeneration - Olga Urbanek; Maryla Moczulska-Heljak; Mikołaj Wróbel; Andrzej Mioduszewski; Dorota Kołbuk (Biomedicines, 2023)
The Anterior Cruciate Ligament (ACL) is one of the major knee ligaments, one which is greatly exposed to injuries. According to the British National Health Society, ACL tears represent around 40% of all knee injuries. The number of ACL injuries has increased rapidly over the past ten years, especially in people from 26–30 years of age. We present a brief background in currently used ACL treatment strategies with a description of surgical reconstruction techniques. According to the well-established method, the PubMed database was then analyzed to scaffold preparation methods and materials. The number of publications and clinical trials over the last almost 30 years were analyzed to determine trends in ACL graft development. Finally, we described selected ACL scaffold development publications of engineering, medical, and business interest. The systematic PubMed database analysis indicated a high interest in collagen for the purpose of ACL graft development, an increased interest in hybrid grafts, a numerical balance in the development of biodegradable and nonbiodegradable grafts, and a low number of clinical trials. The investigation of selected publications indicated that only a few suggest a real possibility of creating healthy tissue. At the same time, many of them focus on specific details and fundamental science. Grafts exhibit a wide range of mechanical properties, mostly because of polymer types and graft morphology. Moreover, most of the research ends at the in vitro stage, using non-certificated polymers, thus requiring a long time before the medical device can be placed on the market. In addition to scientific concerns, official regulations limit the immediate introduction of artificial grafts onto the market.